ANIMASI 3D TOPENG MALANG SEBAGAI KOMUNIKASI VISUAL BUDAYA - Yuwono Fora, Krisna; Widiyanto, Agung Susetyo (Sintesa, 2025)
This research aims to examine the utilization of 3D animation as a visual communication medium in introducing and preserving the culture of Topeng Malang. Topeng Malang is one of the intangible cultural heritages that has high philosophical, aesthetic, and historical values, but its existence has begun to be eroded by the times and the lack of exposure among the younger generation. The method used in this research is a qualitative-descriptive approach with the stages of data collection through literature study, observation, and interviews with local artists and cultural experts. The results show that 3D animation is able to effectively represent the visual and narrative characteristics of Topeng Malang, and has great potential as a medium for cultural education and promotion in modern digital platforms. By combining traditional elements and contemporary visual technology, 3D animation becomes a bridge of cultural communication that is engaging, informative, and easily accessible to the wider community, especially the younger generation.